Rapid Determination of Vitamin B2 in Foods by HPLC with in Capillary Optical Fiber Laser-Induced Fluorescence Detection Technique - Tang, Y.; Zhang, J.; Teng, L.M.; He, Y.Y.; Xiao, D. (Asian Journal of Chemistry, 2014)
In this paper, HPLC with in-capillary optical fiber laser-induced fluorescence (HPLC-ICOF-laser induced fluorescence) detection method has been developed for determination of vitamin B2 (riboflavin). The HPLC separation of vitamin B2 in foods and the ICOF-laser induced fluorescence detection system are studied and optimized. Optimum separation conditions are: mobile phase consisted of methanol/distilled water was 6:4(v/v)in Zorbax Eclipse XDB-C18 column, flow rate was constant at 1 mL min-1, the injection volume was 20 μL. The ICOF-laser induced fluorescence detection system comprises a 530 μm capillary and a 380 μm optical fiber. This method is not only relatively simple chromatographic conditions but also high sensitivity and good precision. It reduces the limit of detection to 0.2 nM and expends the linear range to 0.35-177.14 nM. The correlation coefficient in this range was 0.999. This method can be used in the analysis of trace riboflavin in the food.